Operational procedure sharing pathway in veno-occlusive disease: a Delphi consensus-based recommendations - Francesca Bonifazi; Federico Ravaioli; Anna Paola Iori; Giuseppe Milone; Attilio Olivieri; Arcangelo Prete; Domenico Russo; Stella Santarone; Simona Sica; Simona Sica; Marco Zecca; Antonio Colecchia (Frontiers in Oncology)
BackgroundThe hepatic Veno-Occlusive Disease (VOD), also known as Sinusoidal Obstruction Syndrome (SOS), is a serious complication that can occur after high-dose chemotherapy and hematopoietic stem cell transplantation (HSCT). In Italy, the approach to VOD varies due to differences in healthcare practices and diagnostic criteria among different regions.Aim and methodsTo address this issue, a structured, multi-step Delphi consensus project was undertaken with the aim of standardizing the diagnostic and therapeutic pathways for VOD in Italian clinical practice. The project involved a methodologist, a scientific board of 10 experts, and an expert panel of 45 specialists from Italian hospital centers. This 12-month process included independent contributions, harmonization by a methodologist, and discussions through web meetings.ResultsThe survey identified 15 clinical topics divided into five key areas, including pre-HSCT patient evaluation, clinical-laboratory aspects for diagnosis and therapy, integration of clinical evaluations with EBMT criteria, monitoring with imaging techniques, and adherence to guidelines for managing defibrotide therapy. Key findings include the recommendation of weekly imaging even when VOD is not clinically suspected, the importance of early diagnosis and treatment with defibrotide, and the need for a standardized approach across different centers.ConclusionThe Delphi consensus revealed significant variability in the management of VOD across Italian centers and emphasized the necessity of a multidisciplinary approach involving hematologists, hepatologists, and radiologists. Establishing a national network for sharing best practices and utilizing advanced imaging technologies is essential for improving VOD diagnosis and treatment. The findings indicate the importance of implementing standardized protocols and continuous education to enhance patient outcomes in HSCT settings.